Mitochondrial abnormalities and disruption of the neuromuscular junction precede the clinical phenotype and motor neuron loss in hFUSWT transgenic mice. (28th November 2017) - So, Eva; Mitchell, Jacqueline C; Memmi, Caroline; Chennell, George; Vizcay-Barrena, Gema; Allison, Leanne; Shaw, Christopher E; Vance, Caroline
Abstract: FUS (fused in sarcoma) mislocalization and cytoplasmic aggregation are hallmark pathologies in FUS-related amyotrophic lateral sclerosis and frontotemporal dementia. Many of the mechanistic hypotheses have focused on a loss of nuclear function in the FUS-opathies, implicating dysregulated RNA transcription and splicing in driving neurodegeneration. Recent studies describe an additional somato-dendritic localization for FUS in the cerebral cortex implying a regulatory role in mRNA transport and local translation at the synapse. Here, we report that FUS is also abundant at the pre-synaptic terminal of the neuromuscular junction (NMJ), suggesting an important function for this protein at peripheral synapses. We have previously reported dose and age-dependent motor neuron degeneration in transgenic mice overexpressing human wild-type FUS, resulting in a motor phenotype detected by ∼28 days and death by ∼100 days. Now, we report the earliest structural events using electron microscopy and quantitative immunohistochemistry. Mitochondrial abnormalities in the pre-synaptic motor nerve terminals are detected at postnatal day 6, which are more pronounced at P15 and accompanied by a loss of synaptic vesicles and synaptophysin protein coupled with NMJs of a smaller size at a time when there is no detectable motor neuron loss. These changes occur in the presence of abundant FUS and support a peripheral toxic gain of function. This appearance is typical of a 'dying-back' axonopathy, with the earliest manifestation being mitochondrial disruption. These findings support our hypothesis that FUS has an important function at the NMJ, and challenge the 'loss of nuclear function' hypothesis for disease pathogenesis in the FUS-opathies.